Features of Metal Hydrogenation during Electron Irradiation; Condensed Matter; Vol. 3, iss. 2 - Larionov V. V. Vitaliy Vasilyevich; Tyurin Yu. I. Yuri Ivanovich; Murashkina T. L. Tatiana Leonidovna; Sigfusson T. I. Torsteinn Ingi (2018, 2018)
Title screen